Trade statistics of the Irish Free State in 1924 - Oldham, C. H. (Statistical and Social Inquiry Society of Ireland, 1925)
At the outset of his Essay, Mr. Hooper gives us new information regarding three matters, viz.? Import and Export figures for (i) Transit Trade, which passes across without coming into ownership in this country, (the total value, both ways via Greenore, is only #889,951); (ii) Movements of Bullion and Specie, which is merely an export of worn silver coins; (iii) Parcel Post Trade in nondutiable goods (N.B., the parcel post trade in dutiable goods, being known, was already included in the Trade Statistics), of which an import, "estimated" (by samples) at #3,078,985,, is balanced by an export, "declared" at #1,832,348. We learn that the tables (comprising a Total Trade of merchandise valued at #115,563,719) are defective, by reason of this omission of non-dutiable parcel post, to this amount, namely, #4,911,333? yet Mr. Hooper calls this small figure "an appreciable part" of the trade. Let us be happy with him that he has caulked up that leak.
Symposium on the trade statistics of the Irish Free State in 1924
Read Friday, 15th May, 1925
Keywords: Trade statistics; Irish Free State; 314.15